IMPROVED CUT FLOWER AND CORM PRODUCTION BY EXOGENOUS MORINGA LEAF EXTRACT APPLICATION ON GLADIOLUS CULTIVARS - Adnan Younis; Muhammad Saleem Akhtar; Atif Riaz; Faisal Zulfiqar; Muhammad Qasim; Amjad Farooq; Usman Tariq; Muhammad Ahsan; Zahid Mukthar Bhatti (Acta Scientiarum Polonorum: Hortorum Cultus, 2018)
Bio-stimulants are in excessive demand for the sustainable production of floriculture crops. The current investigation was designed to find out the effect of naturally occurring growth stimulant moringa leaf extract (MLE) on the growth, flowering, post-harvest life and corm production of two gladiolus cultivars (cvs.) ‘Rose Supreme’ and ‘White Prosperity’. The research trial was laid out in the factorial arrangement under randomized complete block design. Corms were grown in the open field under local climatic conditions of Faisalabad, Pakistan. Potential of exogenously applied (MLE; 30 times diluted) was evaluated. Treatments including spraying MLE at 3 leaves, 5 leaves, floral bud stage, one combination of these three stages relative to control with no foliar application. Application of natural bio-stimulant produced maximum height in both cvs. against T4. Both cvs. gave maximum stalk length in response to T4. The number of florets spike–1 found the maximum (13) in T1 compared to control T0 which yield (9) florets. Maximum vase life in sucrose solution (13.33 days) was exhibited by T1 for both cvs. while minimum (10 days) in T0.  In cultivar comparison earlier spike emergence was observed in ‘White Prosperity’. In ‘Rose Supreme’ maximum corm weight was attained in response to T3 (43.43 g) while minimum (30.33 g) in T0.‘White Prosperity’ produced maximum weight (40.33 g) against T4 whereas minimum by control. The cultivar mean comparison showed the superiority of cormel diameter in ‘Rose Supreme’ (10.93 mm) than ‘White Prosperity’ (9.13 mm). In treatment comparison, T4 produced maximum diameter (12.04 mm) in ‘Rose Supreme’ moreover, T2 induced maximum (9.57 mm) diameter in ‘White Prosperity’.